Obesity during Adolescence and Feeding Practices during Infancy: Cross-Sectional Study - Reem Sharaf-Alddin; Radhia Almathkoori; Hara Kostakis; Ahmed N. Albatineh; Abdullah Al-Taiar; Muge Akpinar-Elci (MDPI AG, 2023)
Background: Breastfeeding is proposed to play a role in reducing the risk of obesity throughout life. Kuwait has an extremely high prevalence of childhood obesity (45% of adolescents are overweight/obese) and extremely low breastfeeding indicators, particularly exclusive breastfeeding. In fact, little is known about the association between breastfeeding and obesity from Kuwait and the broader Middle East. Aims: To estimate the prevalence of overweight/obesity in female adolescents in Kuwait and assess its association with breastfeeding during infancy. Methods: This is a cross-sectional study that included 775 girls randomly selected from public and private high schools in Kuwait. The primary exposure was breastfeeding in the first four months of life, and the outcome was overweight/obesity during adolescence. Multivariable logistic regression was used to assess the association between breastfeeding and overweight/obesity while adjusting for potential confounders. Results: Approximately 45% of adolescent girls were either overweight/obese. We found no significant association between breastfeeding (exclusive/mixed breastfeeding and formula feeding/no breastfeeding) and overweight/obesity neither in univariable analysis (Crude Prevalence Ratio: 1.14, 95%CI [0.92-1.36] & Crude Prevalence Ratio: 1.29, 95%CI [0.86-1.68]; p = 0.293) for mixed feeding and no breastfeeding respectively, nor in multivariable analysis (Adjusted Prevalence Ratio: 1.14, 95%CI [0.85-1.42] & Adjusted Prevalence Ratio: 1.20, 95%CI [0.68-1.68]; p = 0.589) for mixed feeding and no breastfeeding respectively. Conclusion: Breastfeeding during infancy was not significantly associated with overweight/obesity during adolescence. However, breastfeeding should be encouraged for its indisputable benefits for infants and their mothers alike. Further prospective studies are needed to assess the association.